Learning Mathematics Through the Missori Mathematics Model Project (MMP) Private Elementary School Students PAB 29 Manunggal - Dwi Safitri, Riska (Berpusi Publishing, 2023)
The purpose of this study is to improve student learning activities in mathematics learning through the Missouri Mathematics Project (MMP) model. This research is a Classroom Action Research. The subjects and objects in this study were grade III students of SD Swasta PAB 29 Manunggal. There are 23 students. The instruments used in this study were observation sheets and tests to comply with student learning activities before and after using the Missouri Mathematics Project (MMP) model. The approach in this study uses classroom action research, with the Missouri Mathematics Project (MMP) model, which uses cycle I and cycle II. Student activities include a) answering questions from teachers, before the study 26.08%, Cycle I 60.86%, and cycle II 78.26%, b) submitting a map, before the study 30.43%, Cycle I 69.56%, and Cycle III 82.60%, c) doing questions in front of the class, before the research 17.39%, Cycle I 73.91%, and Cycle II 86.95%, d) expressing their ideas or opinions, before the researcher 21.73%, Cycle I 65.21%, Cycle II 78.26%, e) doing practice questions, before the study 39.13%, Cycle I 78.26, and Cycle II 86.95%. Cycle I with an average score of 61.08 and those who get a score of 75 there are 4 students while those who fail number 19 people and Cycle II get an average score of 85.21, students who get more than 75 there are 20 students and those who fail number 3 students. From the results of this research, researchers concluded that by applying the Missouri Mathematics Project (MMP) model can improve student learning activities.